On sub-ideal causal smoothing filters - Dokuchaev, Nikolai (Elsevier BV, 2012)
Smoothing causal linear time-invariant filters are studied forcontinuous time processes. The paper suggests a family of causalfilters with almost exponential damping of the energy on the higherfrequencies. These filters are sub-ideal meaning that a fasterdecay of the frequency response would lead to the loss of causality.